The Philosopher Focalization in the Novel Orbital by Samantha Harvey - Cahyani, Nugrahaning Anindita; Widyatwati, Ken; Suryadi, M; Nurulhady, Eta Farmacelia (HUMANIKA, 2026)
This article examines how focalization employed to shape what and how events, perceptions, and private thoughts are disclosed to the narratee. The object of this study is Orbital by Samantha Harvey that surrounds the six astronauts living in the International Space Station. The analysis applies Mieke Bal’s focalization framework to selected passages, identifying focalizers, focalized objects, and shifts among external-bound, character-bound, and embedded focalization. The analysis also uses close reading focusing on how the narrator’s selective knowledge, through panoramic framing, direct address, and interruptions of personal thoughts creates interpretive gaps that require narratee participation. The study advances the argument that Orbital leveraging the narrator functioning not only as a storyteller but as a philosophically oriented, phenomenological focalizer who repeatedly reorients attention from the events depicted to the manner in which experience is given.  The findings indicate that external-bound focalization constructs shared horizons of perception, while character-bound focalization concentrates ethical urgency and interpretive uncertainty.  Embedded focalization further intensifies the text’s reflective structure by staging layered access. The conclusion of this studyis that focalization functions as the novel’s main philosophical approach sustaining inquiry rather than closure, and directing narratee toward the constitution of meaning across shifting perspectives. This study posits that focalization can be read as a phenomenologically inflected narrative practice.Keywords: focalization; narratology; phenomenology; Orbital; Samantha Harvey